Microwave devices and circuits - Liao, Samuel Y (Prentice-Hall of India, 2008)
Microwave devices and circuits / Liao, Samuel Y. -- New Delhi: Prentice-Hall of India, 2008 621.3813 L694e3 No. of Copies : 1